2018
DOI: 10.1001/jama.2018.4930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coaching to Increase Water Intake on Kidney Function Decline in Adults With Chronic Kidney Disease

Abstract: clinicaltrials.gov Identifier: NCT01766687.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 41 publications
1
67
0
1
Order By: Relevance
“…Recently, in a 5 year prospective study of non‐CKD and non‐diabetes adults ( n = 12 041), Kuwabara et al show that serum Na + concentration (in the range of 137–147 mmol/L) and calculated serum osmolality, despite falling within reference range, are positively associated with a cumulative incidence of CKD (eGFR of <60 mL/min per BSA) . A recent multicenter interventional study of CKD stage 3 patients (n = 631) showed a smaller decline in serum creatinine clearance (no significant change in the eGFR) resulting from a one‐year increase in self‐reported fluid intake by 0.6 to 0.8 L/day; this was associated with a reduction in serum copeptin (‐2.2 pmoL/L) …”
Section: Combined Salt Overconsumption and Under‐hydration (Suboptimamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in a 5 year prospective study of non‐CKD and non‐diabetes adults ( n = 12 041), Kuwabara et al show that serum Na + concentration (in the range of 137–147 mmol/L) and calculated serum osmolality, despite falling within reference range, are positively associated with a cumulative incidence of CKD (eGFR of <60 mL/min per BSA) . A recent multicenter interventional study of CKD stage 3 patients (n = 631) showed a smaller decline in serum creatinine clearance (no significant change in the eGFR) resulting from a one‐year increase in self‐reported fluid intake by 0.6 to 0.8 L/day; this was associated with a reduction in serum copeptin (‐2.2 pmoL/L) …”
Section: Combined Salt Overconsumption and Under‐hydration (Suboptimamentioning
confidence: 99%
“…51 A recent multicenter interventional study of CKD stage 3 patients (n = 631) showed a smaller decline in serum creatinine clearance (no significant change in the eGFR) resulting from a one-year increase in self-reported fluid intake by 0.6 to 0.8 L/day; this was associated with a reduction in serum copeptin (-2.2 pmoL/L). 52 SUMMARY Na + and water regulation is complex, involving neurohumeral multi-organ regulations of AVP, glucocorticoids, RAAS activation, muscle catabolism, urea generation and salt-retention. Several lines of evidence lend strong support to a pathogenic role of high-salt and low-water intake, common in the general population, 17 in the genesis of HTN and CKD.…”
Section: Combined Salt Overconsumption and Under-hydration (Suboptimamentioning
confidence: 99%
“…Recent short‐term clinical trials have shown that increased water intake can reduce concentrations of plasma copeptin, fasting blood glucose and glucagon in healthy participants . Another study also found that increased water consumption resulted in decreased copeptin concentrations in participants with chronic kidney disease, however, no differences in rates of eGFR decline were observed in participants with or without increased water intake …”
Section: Discussionmentioning
confidence: 96%
“…13,49 Another study also found that increased water consumption resulted in decreased copeptin concentrations in participants with chronic kidney disease, however, no differences in rates of eGFR decline were observed in participants with or without increased water intake. 50 Mechanisms leading to increased AVP, and thus copeptin, in diabetes are also incompletely elucidated. Our results showed that copeptin positively correlated with HbA1c in adolescents with T1D…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the potential therapeutic role of water intake and hydration in CKD and ADPKD. While a pilot study involving stage 3 CKD patients documented that increasing water intake increased urine volume and lowered plasma copeptin [63], a larger-scale randomized controlled trial failed to show that an increase in water intake slowed the progression of the disease [64]. However, the increase in urine volume was quite modest (+0.6 L.d) and the follow-up time relatively short.…”
Section: Water Intake As a Potential Therapeutic Target For Renal Dismentioning
confidence: 98%